Public Transport Strikes and Their Relationships With Air Pollution, Mortality, and Hospital Admissions. Issue 2 (30th September 2019) - Triguero-Mas, Margarita; Martínez-Solanas, Èrica; Barrera-Gómez, Jose; Agis, David; Pérez, Noemí; Reche, Cristina; Alastuey, Andrés; Querol, Xavier; Pérez, Katherine; Basagaña, Xavier
Abstract: There is limited suggestive evidence of relationships between public transport strikes and either increased air pollution or worse population health. In this study we aimed to assess whether public transport strikes were associated with increases in health events (overall, cardiovascular and respiratory mortality, and cardiovascular and respiratory hospitalizations). We also explored whether air pollution mediated those associations. We used data from the city of Barcelona (Spain) for the period 2005–2016 on strikes, health events, and ambient air pollution (nitrogen dioxide, nitrogen monoxide, particulate matter (PM) with an aerodynamic diameter ≤10 μm, PM with an aerodynamic diameter ≤2.5μm, PM with an aerodynamic diameter ≤1μm, number of particles with a diameter greater than 5 nm per cm 3 (particle number concentration), and black carbon). We used linear and quasi-Poisson regression models to explore the associations between air pollution and public transport strikes and between public transport strikes and health outcomes. We also investigated potential causal mediation by air pollution. Overall, this study suggested that public transport strikes are associated with increased overall mortality, respiratory mortality, and respiratory hospitalizations. However, our findings suggest that such increases are not mediated by the increase in air pollution. Our results indicate the need to further investigate these relationships and potential mechanisms.